Morphological Characteristics and Identification of Key Genes Regulating Distyly Morph in Primula vulgaris - Xuan Wang; Hantao Sun; Yan Xu; Feng Cao; Yanlong Wang; Jianbin Ma; Jinfeng Li; Liu Liu; Ping Li; Xiaoman Zhang (Agronomy)
The Primula vulgaris, belonging to the genus Primula, is a typical distyly. The distyly is an important morphological feature in nature. However, there is a shortage of research on the causes of distyly formation and the associated genes that control this trait. In this study, we took P. vulgaris as the experimental material, observed the floral morphological features, made paraffin sections, and performed transcriptome analysis of the styles. The results of morphological observations indicated that the L-morph and S-morph showed dimorphism in flower characteristics, the stigma height was 1.35 cm and the anther height was 0.72 cm for the L-morph and 0.71 cm and 1.50 cm for the S-morph. From the paraffin sections, it can be observed that the papillocytes and stylocytes of the L-morph are longer than those of the S-morph. A total of 2822 DEGs were obtained in the analysis of DEGs, among which 2038 genes were up-regulated and 786 genes were down-regulated. The DEGs of the two morphs were mainly enriched in biological processes such as phenylpropanoid biosynthesis and plant hormone signal transduction. BACOVA_02659 was highly expressed in the L-morph and might hydrolyze and activate growth factors, which were present in the phenylpropane biosynthetic pathway. DEGs such as BoGH3B, SAUR21, and SAUR50 may be involved in the development of long and short styles, which in turn leads to the presentation of differences between long and short morphs. These results provide new insights into the molecular mechanism of Primula.